Pendampingan Siswa yang Berkesulitan Belajar Matematika Materi Turunan Kelas XI MIA 2 MAN 1 Sungai Penuh - Rahayu, Atika; Sari, Nada Afrima; Putra, Aan (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Learning difficulties are a major problem in the learning process, especially in learning mathematics. This is felt by several students in class XI MIA 2 MAN 1 Sungai Penuh, where there are several students who have difficulty in understanding mathematical concepts, difficulty in acquiring the ability to read, write, or speak fluently and effectively, and limited learning time. Therefore. this mentoring aims to help individuals achieve better learning outcomes. With learning assistance, it is hoped that they can overcome the difficulties or obstacles they face in understanding the material. The mentoring method consists of three stages, namely preparation or preliminary study, implementation of mentoring and evaluation of activities. Assistance is provided to 5 students who need assistance because of their poor understanding of the material being studied. From the results of the assistance, it was found that math learning assistance greatly helped students in understanding and mastering mathematical concepts through more focused explanations and individualized support.